Cationic all-halogen bonding rotaxanes for halide anion recognition - Li, X; Lim, J; Beer, P (Royal Society of Chemistry, 2017)
A family of cationic halogen bonding [2]rotaxanes have been synthesised via an active-metal template synthetic strategy. 1H NMR spectroscopic anion titration investigations reveal these interlocked host systems recognize halides selectively over oxoanions in aqueous-organic solvent media. Furthermore, systematically modulating the rigidity and size of the rotaxanes’ anion binding cavity via metal complexation, as well as by varying the number of halogen bond-donor groups in the axle component, was found to dramatically influence halide anion selectivity.